Induction of EMS (Ethyl Methanesulfonate) Chemical Mutations on Hemp Seed Germination (Boehmeria nivea L.) - Siti Nur Azizah; Widiwurjani (Future Science, 2023)
A Hemp plants are plants that have not been much research and exploration. Propagation of flax plants can be carried out by propagation of rhizomes. Other propagation can use cuttings of rootstocks, middle stems, and shoots, although such propagation is not yet optimal and has a presentation of about 60% on its failure. Genetic diversity in hemp plants aims to increase germplasm. Genetic diversity in multiplying germplasm means to increase the collection of hemp plants. Environmental changes in plant populations can be overcome by genetic diversity. This study aims to identify the germination and success of EMS chemical mutations in the results of hemp plant seed mutations (Boehmeria nivea L.). Observations were made on several hemp seed accessions, namely Kumamoto (KM), Bandung A (BDA), Lembang A (LA), Indochina (IDC) and Seiki Selskin (SS). Observational measurements were carried out when the seeds were 7, 14, and 21 DATT with parameters of percentage of germinated seeds and percentage of mutation results. From the observations, the highest percentage was obtained in 2 accessions, namely Bandung A (BDA) and Lembang A (LA) with a percentage of 41.3%. The lowest percentage was found in Indochina's accession with a presentation of 29.3%. The percentage of inhibited germination was highest in EMS treatment of 0.25% with a soaking period of 6 hours. When compared again with treatment control which is almost close to the percentage of germination is at a soaking duration of 3 hours.